Problems of Infertility Patients Not Benefited by Insurance (BPJS) - Nunung Sri Wahyuni; Ferry Armanza (PT FORMOSA CENDEKIA GLOBAL, 2023)
The Health Social Security Administering Body or BPJS Health is a State-Owned Enterprise (BUMN) that provides health and social security for all Indonesian people. This legal entity started operating in 2014 where its function and authority are to provide social security in the form of health insurance for the general public and workers to improve their welfare. The research method used is a literature study research system where research is carried out by searching, reading, recording, and analyzing findings in the field related to written sources such as books, journals, archives, articles, or magazines that correlate with the problems being studied. So that it can be evidence to strengthen the argumentation statement presented. Infertility is a global issue that is currently being discussed, it is because this type of health problem is experienced by 22.3% of people in the world. Based on the urgency, several countries have started to provide insurance for their citizens related to health problems. Currently, only 16 states have infertility coverage for private insurance companies. This is because the very high cost makes not many insurance companies dare to guarantee this infertility health problem.